PENGARUH KEPRIBADIAN WIRAUSAHA DAN KOMPETENSI PRODUK KREATIF & KEWIRAUSAHAAN TERHADAP MINAT BERWIRAUSAHA SISWA PROGRAM KEAHLIAN BISNIS DAN PEMASARAN SMK NEGERI 1 PEKANBARU - Dwi Afriani; Syakdanur Nas; RM Riadi RM Riadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research aims to determine whether entrepreneurial personality, creative product competencies and entrepreneurship influence the interest in entrepreneurship in class XII business and marketing expertise programs at SMKN 1 Pekanbaru in 2020. This type of research is quantitative research. The population of this research is 61st grade students of business and marketing expertise program at SMKN 1 Pekanbaru, amounting to 61 students. The sampling technique uses a saturated sample technique. Data collection techniques using questionnaires/ questionnaires and documentation and data analysis method using descriptive statistical analysis and path analysis. The results of this study are entrepreneurial personality, creative product competence and entrepreneurship have a significant effect simultaneously. Entrepreneurial nature partially influences significantly and the ability of creative and entrepreneurial products partly has a significant effect. The conclusion of this study is the entrepreneurial personality, creative product competencies and entrepreneurship have a significant impact both simultaneously and partially. This research suggests is that the inculcation of entrepreneurial personality values can be improved and the teacher can improve the quality of entrepreneurship education received by students in providing entrepreneurial knowledge and skillsKey Words: Entrepreneurial Personality, Creative Product and Entrepreneurial Competency, and Entrepreneurship Interest